(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Nuove rivendicazioni di differenze negli U.S.A. e in Europa: un tentativo di comparazione - 2. I conflitti generati dal Contraception Mandate negli U.S.A. – 3. Il caso Zubik v. Burwell – 4. La difficile definizione del concetto di substantial burden – 5. La soluzione di compromesso adottata dalla Corte Suprema - 6. Accomodazionismo religioso e nuove “battaglie culturali” - 7. Prerogative dei soggetti confessionalmente connotati e “costi sociali” del loro riconoscimento - 8. Il fenomeno delle nuove conscience claims - 9. La valutazione dei third-party burdens - 10. Il diritto all’obiezione di coscienza dinanzi alla Corte di Strasburgo - 11. La decisione Eweida and others v. United Kingdom e l’ampliamento della portata dell’art. 9 CEDU - 12. Il rilievo attribuito al principio di non discriminazione - 13. La valorizzazione del margine di apprezzamento - 14. Annotazioni riepilogative. New forms of Conscientious Objection between Burdens on Religious Freedom and Third-Party Burdens. A Comparative Analysis of the Supreme Court USA and of the Court of Strasbourg Case Law Abstract: This paper analyzes the emerging tension between new complicity-based conscience claims of accommodation and the costs associated with them, in the ambit of the current national constitutional and international law frameworks. In a comparative perspective, recent decisions of the U.S. Supreme Court and of the European Court of Human Rights will be examined. The U.S. Supreme Court is moving towards a greater recognition of religious freedom in its collective dimension in the ambit of a common law framework; the European Court of Human Rights is entrusted with the delicate balance between unity and diversity, without unduly interfering with the national identities and legal regimes recognized to the Churches.